Indicadores de condições de trabalho: percepção dos atores sociais - Lahoz, Manoela de Assis (Universidade Federal de São Carlos, 2012)
The overlap of experiences from work, with those coming from outside, generates wear on people's health, and negative indices of health and well-being can harm both operators and the company, such as decreased productivity, absenteeism and decreased resources for the organization. In this context, it becomes important to understand how companies deal with this concern in relation to working conditions. This concern is seen in some international institutions, as well as Brazilian law, through services, programs and indicators related to working conditions. Therefore, the main objective of this study was to identify the perceptions of different social actors of the company about indicators and factors that influence working conditions. We used the case study in a multinational company in the state of São Paulo, in which 70 interviews were conducted with three specific groups: members of CIPA, SESMT professionals and a group of operators. In the interviews was administered a questionnaire consisting of open and closed questions and indicators related to working conditions. The results of this study showed that different groups of social actors of the company have different perceptions in relation to indicators and working conditions. On one hand, the perception of who participates in the activity, such as the group of operators, which had a perception more related to activity on the factors that influence health. Moreover, groups and CIPA SESMT focus their perception on task, and how much activity is carried away from the task or standards. Furthermore, we noted two interesting aspects: that the main concerns of these actors in relation to working conditions focuses primarily on occupational safety and also the distance of health professionals SEMST with the work environment and activity. Therefore, it is concluded that the professional services of the members of legislative agencies of the company, as SESMT and CIPA is very similar, with an eye to legislation and compliance task, unlike operators, which are very close to the activity, which provides a good insight regarding working conditions and factors present in the workplace. This study also emphasizes the importance of a professional health care more active in the workplace and in SESMT.
Keywords: Trabalho - condições; Indicadores de desempenho; Percepção; Indicators; Working Conditions; Perception; ENGENHARIAS::ENGENHARIA DE PRODUCAO